PRESIDENT PERMISSION TO THE INVESTIGATION OF STATE OFFICERS ON MALADMINISTRATION ACTION - Muh Sabaruddin Sinapoy (Universitas Airlangga, 2016)
The purpose of writing this journal is to find out that permits is a juridical instrument used by the government to influence the people to want to follow the recommended way to achieve a concrete goal. Permission serves as the spearhead of the legal instrument as advisors, engineers and designers. Permits can be used as a control instrument and an instrument to realize good governance, structuring and regulation of these permits are supposed to be done as the realization of governernment function related to the inspection of state official by law enforcement official. The research methods utilized is a normative method which involved the method of regulatory analysis and conceptual analysis. This research confirms that presidential permit for the examination and summon of public official are indeed needed and necessary, which can be formulated through special law and regulations on the procedures of examination permit, which are to be synchronized with other related laws and regulations. President Permission, when viewed from the standpoint of administrative law has meaning as preventive instrument used for protect President that the governance and functioning of public service at the central and local government. This research recommends for a formation of special court which can take place through a forum privilegiatum, under the Supreme Court to allow for recognition of the state official´ positions, statuse,s and dignities.